Das Bild des Bischofs Carl Maria Splett im historischen Gedächtnis in Polen und in Deutschland - Kmak-Pamirska, Aleksandra (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
Over the years the opinions about Bishop Carl Maria Splett have varied; the bishop has been surrounded by a lot of controversy. The conduct of the Bishop of Gdańsk during the Second World War is far from unequivocal. Everything depends on the point of view. In her brief article the author examines the evolution of the historical memory of Bishop Carl Maria Splett and its transformations over the years in Poland and Germany. The memory of Bishop Splett has evolved differently in both these countries. Before 1989 he was seen in Poland as an enemy of Polishness and a Hakatist. After the political transformations in the early 1990s he began to be viewed in a more positive light. In Germany, on the other hand, the historical memory of Bishop Splett was and still is very positive. However, in the 1960s and 1970s the image of Bishop Splett was more apologetic than it is now. To sum up, it could be said that today the image of Bishop Carl Maria Splett in the historical memory in Poland and Germany has become very homogeneous.
Keywords: pamięć historyczna; Splett, Carl Maria, biskup; II wojna światowa; narodowy socjalizm; gdańscy katolicy